(untitled) (Journal of Parents and Teachers, 2014)
The offer of books for children and young people has been increased in recent years. The book is sold as one more product and is very conditioned by the advertising and by the layout that is made of it. In order to choose good books for the youngest, the article proposes varied criteria that have to do with age, psychology, values teaching, illustrations or linguistic quality.